Análise das topografias de controle de estímulos envolvidas em escolhas de acordo com o modelo em indivíduos com Síndrome de Down - Vasconcellos, Mariliz (2009)
The formation of equivalent stimuli classes is a psychological phenomenon that has important characteristics for the experimentation of processes involving symbolic behavior acquisition. This kind of behavior has been the target of a wide variety of contemporary studies which have also demonstrated the possibility of such approach to generate symbolic behavioral repertoires based only on the teaching of some relations between stimuli. It is vital to investigate the parameters that optimize the establishment of equivalent stimuli classes desired by the researcher when defining the behavior to be installed through the procedure of matching-to-sample (MTS). Studies in the area have widely shown that after training A1B1 and B1C1, there is an emergency of some relations, such as B1A1, C1B1, A1C1 and C1A1, which demonstrate, respectively, the properties of reflexivity, symmetry, transitivity and equivalence. One of the parameters that determine the effectiveness of a procedure on class formation is the type of control relation exercised by the comparison stimuli in MTS attempts. Therefore, the present study aimed to identify the role of specific types of training of conditional discriminations in the establishment of relations of control for selection and rejection. Study participants were two teenagers with Down syndrome. The training consisted on MTS sessions with and without mask in two training types: non-nodular and nodular. The former occurred by presenting stimuli which function was either model or comparison only, and the latter was characterized by presenting stimuli with dual function, i.e. model and comparison simultaneously. Verification testing of the control relations established at baseline was made after non-nodular training and after nodular training, and only then verification testing of behavioral emergency was made. Two stimuli sets involved attempts with mask, while other two consisted of attempts without a mask. The experiment was specifically designed in a way that the training of a stimuli set with mask has occurred almost simultaneously with the training of a stimuli set without mask. Thus, the influence of historical undesirable variables was avoided on deductions made from performance comparison of the two different attempts (with or without mask). Results demonstrated, generally, that the training procedure used was very effective in teaching and formation of classes, what made difficult even to compare the greater effectiveness of the procedures with or without use of mask in the training of conditional relations. It is suggested the replication of this study, with a larger number of participants of this same population, so that it is possible to evaluate the data generality.